Influence of physicochemical environmental factors on morphometric characteristics of macroalgae from Ambon Island, Indonesia - SINTJE LILINE; DOMINGGUS RUMAHLATU; SITI ZUBAIDAH; SRIYANTI SALMANU; Kristin Sangur (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Liline S, Rumahlatu D, Zubaidah S, Salmanu S, Sangur K. 2024. Influence of physicochemical environmental factors on morphometric characteristics of macroalgae from Ambon Island, Indonesia. Biodiversitas 25: 1436-1453. Macroalgae are an essential part of the marine biodiversity of Ambon Island, requiring thorough investigation for conservation and cultivation purposes. Therefore, this study aimed to identify macroalgae and analyze the relationship of environmental physicochemical factors to morphometric characteristics of macroalgae from the coastal waters of Ambon Island, Maluku Province, between June and July 2023. Sampling was performed at four locations, i.e., Hutumuri, Alang, Aer Low, and Suli Villages, followed by laboratory morphometric identification and measurements. The results showed significant variations in the physicochemical environmental factors of the four locations, featuring temperatures ranging from 25.00-30.05°C, pH of 7.00-8.34, salinity of 31.00-32.00, and dissolved oxygen (DO) of 6.00-15.27. Furthermore, the substrate in each location differed, presenting sequentially as sandy coral, coral, sandy coral, and mud sand. 11, 10, 6, and 25 species were found in Hutumuri, Alang, Aer Low, and Suli, respectively. Each species, with distinct morphological characteristics and morphometric sizes, was distributed across the Chlorophyta, Ochrophyta, and Rhodofhyta classes. These observations provided crucial insights into the intricate relationship between environmental factors and morphometric characteristics, including full length, thallus width, and length, as well as holdfast length and width of both same-species and different macroalgae populations in Ambon Island.